"Securitized" UK aid projects in Africa: Evidence from Kenya, Nigeria and South Sudan. (6th July 2021) - Petrikova, Ivica; Lazell, Melita
Abstract: Motivation: In 2020, the UK Department for International Development (DFID) was merged with the Foreign and Commonwealth Office (FCO) as the Foreign, Commonwealth and Development Office (FCDO). This policy move strengthens the trend to "securitize" development, whereby the provision of aid is motivated by national security concerns. Purpose: Many researchers have raised concerns about the securitization of aid and its consequences for development, but little research has examined its impact on aid‐recipient countries. Approach and Methods: This study evaluates 144 securitized aid projects implemented by DFID between 2000 and 2018 in Kenya, Nigeria and South Sudan, using the Organisation for Economic Co‐operation and Development (OECD) evaluation criteria of relevance, effectiveness, impact, and sustainability. Findings: Our analysis finds that although most of the projects assessed were "relevant", i.e. formally aligned with recipient and funders' objectives, many struggled to achieve their intended outputs ("effectiveness"). Few of the projects had a positive "impact". We conclude that the securitized projects reviewed did not significantly strengthen the recipient countries' institutions, stability, or security but had some negative side effects. Policy Implications: In view of the merger of DFID with the FCO and the decision to reduce aid from 0.7% to 0.5% of Gross National Income (GNI), the UK is likely to draw an even closer connection between domestic security priorities and its development aid. In view of our empirical findings, the UK government needs to be more aware of the limitations of development interventions undertaken in the name of security and consider other means of enabling development.